Whispers of wisdom: exploring the essence of Partandaan in the Suluk indigenous mediation - Nurhasan Danial; Asmiaty Amat; Nelson S. Dino (University of Southeastern Philippines, 2024)
The Orang Suluk, who call themselves Tausug, have a deep history in the sea areas and are known for their strong cultural and political independence. Residing in the Sulu Archipelago and the northeastern coast of Borneo, they identify themselves by names such as Suluk, Anak Negeri, coastal people, sea people, indigenous maritime group, and Orang Asal Pesisir. Symbols are a part of the Suluk Indigenous Mediation (SIM) approach, which is still practiced on the east coast of Sabah, Malaysia. The techniques mentioned are organic to the Adat (customs) of the Suluk passed down from their forefathers. This study discusses the essence of partandaan (symbols) found in SIM practices of the Suluk mediators in the said geographical area. Five expert informants in Semporna, Lahad Datu, and Sandakan shared their wisdom, experience, and interpretation of the SIM during the in-depth interviews as empirical data. The researchers also did library work to collect secondary data. Employing Hewitt’s Symbolic Interactionism (2002), findings revealed that objects, social acts, and language carry symbols that are meaningful to the life of the Suluk. They influence the thinking of the Tausug, maintain the balance and harmony of their day-to-day life, and crystalize the vision of peace, understanding, and forgiveness. Indeed, symbols are fruitful tools for successful culturally and religiously sensitive mediation. The study highlights the significance of symbols in Suluk Indigenous Mediation, suggesting further exploration of cultural variations and the potential integration of symbolic elements into conflict resolution mechanisms.